ANALISIS PEMBIAYAAN PENANGGULANGAN GIZI BURUK PADA BALITA DI KABUPATEN LOMBOK TENGAH PROVINSI NUSA TENGGARA BARAT - Irna Agustina; Toto Sudargo; Diah Ayu Puspandari (Jurnal Manajemen Pelayanan Kesehatan (The Indonesian Journal of Health Service Management), 2021)
Background: According to WHO more than 50% of infant and child mortality is related to malnutrition, a nutritional problem that needs to be solved quickly and appropriately. Based on the results of PSG Kadarzi years 2012-2015 the prevalence of emaciation according to indices of BB /TB or BB/PB was 7,43%, 7,32%, 9,81%, and 7,6%. Those number fluctuate but if this nutritional problem is ignored it will cause problems of development in the future. Consider this phenomenon we can find out how the financing of prevention of malnutrition in Central Lombok regency issued by government and society. Objective: Identify financing countermeasures of malnutrition among children under five years old in the district of Central Lombok, West Nusa Tenggara (NTB) Methods: This research is a descriptive study and crosssectional research design with quantitative dates. This research was conducted in Central Lombok regency, West Nusa Tenggara Province. The subjects of this study were the mother or malnourished children keeper as many as 30 people. The data analysis was conducted by descriptive the financing countermeasures of malnutrition in Central Lombok regency. Results: From the search results and interviews it showed that the malnutrition countermeasures costs spent by the government was IDR2.816.913,00/person/year and the amount of public expenses was IDR7.874.100,00/person/year. The large proportion of the cost of government was 26,35% and by the public was 73,65%. Conclusion: The society expenses were 2,79 times as high as government expenses on malnutrition countermeasures on children under five in Central Lombok regency.